2020
DOI: 10.1002/jor.24844
|View full text |Cite
|
Sign up to set email alerts
|

The knee prosthesis constraint dilemma: Biomechanical comparison between varus‐valgus constrained implants and rotating hinge prosthesis. A cadaver study

Abstract: The real degree of constriction of rotating hinge knee (RHK) and condylar constrained prostheses (CCK) is a matter of discussion in revision knee arthroplasty. The objectives of this study are to compare the tibial rotation of both implants and validate the use of inertial sensors with optical tracking system as movement measurement tools. A total of 16 cadaver knees were used. Eight knees were replaced using a RHK (Endomodel LINK), and the remaining eight received a CCK prosthesis (LCCK, Zimmer). Tibial rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…Rotating hinge prosthesis could provide better three‐dimensional freedom, and has been more frequently chosen for TKA to treat Charcot knee in the last 10 years (Figure 2 ). 20 , 21 Recently, more studies 5 , 6 , 9 , 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 reported the use of condylar constrained prostheses and rotating hinge prostheses with satisfied results for TKA in Charcot knee.…”
Section: Discussionmentioning
confidence: 99%
“…Rotating hinge prosthesis could provide better three‐dimensional freedom, and has been more frequently chosen for TKA to treat Charcot knee in the last 10 years (Figure 2 ). 20 , 21 Recently, more studies 5 , 6 , 9 , 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 reported the use of condylar constrained prostheses and rotating hinge prostheses with satisfied results for TKA in Charcot knee.…”
Section: Discussionmentioning
confidence: 99%
“…However, the introduction of the newer third‐generation RHK allows more rotational freedom, and therefore reduces the constraint in the axial plane [5]. Consequently, a CCK can lead to more constraint in the axial plane compared to an RHK [18], which is investigated by recent cadaver and biomechanical studies demonstrating that some RHK implants (RT‐Plus RHK [7], Zimmer [23], Endomodel LINK [24]) were prone to less stress shear at the bone–implant interface compared to the CCK implant [7, 23, 24]. However, an RHK remains more constrained in the coronal plane compared to a CCK, as the CCK design offers less rigidity during varus–valgus movements [2].…”
Section: Discussionmentioning
confidence: 99%
“…During rTKA, using more constrained implants, such as VVC and hinged prostheses, require femoral and tibial stems [ 3 , 9 ]. Stems have a load-sharing capability, increase initial femoral and tibial component stability, and aid the remaining damaged or absent metaphyseal bone to deal with excessive stress [ 10 ].…”
Section: Discussionmentioning
confidence: 99%